The Effect of Pooling on the Detection of the Nucleocapsid Protein of SARS-CoV-2 with Rapid Antigen Tests - Tim Berking; Sabrina G. Lorenz; Alexander B. Ulrich; Joachim Greiner; Eric Kervio; Jennifer Bremer; Christina Wege; Tatjana Kleinow; Clemens Richert (Diagnostics, 2021)
The COVID-19 pandemic puts significant stress on the viral testing capabilities of many countries. Rapid point-of-care (PoC) antigen tests are valuable tools but implementing frequent large scale testing is costly. We have developed an inexpensive device for pooling swabs, extracting specimens, and detecting viral antigens with a commercial lateral flow test for the nucleocapsid protein of SARS-CoV-2 as antigen. The holder of the device can be produced locally through 3D printing. The extraction and the elution can be performed with the entire set-up encapsulated in a transparent bag, minimizing the risk of infection for the operator. With 0.35 mL extraction buffer and six swabs, including a positive control swab, 43 ± 6% (n = 8) of the signal for an individual extraction of a positive control standard was obtained. Image analysis still showed a signal-to-noise ratio of approximately 2:1 at 32-fold dilution of the extract from a single positive control swab. The relative signal from the test line versus the control line was found to scale linearly upon dilution (R2 = 0.98), indicating that other pooling regimes are conceivable. A pilot project involving 14 participants and 18 pooled tests in a laboratory course at our university did not give any false positives, and an individual case study confirmed the ability to detect a SARS-CoV-2 infection with five-fold or six-fold pooling, including one swab from a PCR-confirmed COVID patient. These findings suggest that pooling can make frequent testing more affordable for schools, universities, and similar institutions, without decreasing sensitivity to an unacceptable level.